Assessment of energy sharing coefficients under the new Portuguese renewable energy communities regulation - Queiroz, Humberto (2023)
The recent published European legal framework (Directives (EU) 2018/2001 and 2019/944) on renewable energy consumption, and its Portuguese transposition (the Decree-Law 15/2022), opens the possibility for buildings to operate as energy communities. One of the objectives is to increase the use of locally generated energy from renewable sources, by sharing available surplus among participants, using sharing coefficients defined by the entire community. Taking the actual legal framework into consideration, this paper presents an analysis of the energy sharing coefficients proposed by the newly published Portuguese legislation via the assessment of a renewable energy community, formed by public buildings, whose operation varies according to different sharing coefficient applied. Results show that time-variable energy sharing coefficients are the best option to the considered renewable energy community. Collected results also show that larger consumers can extract higher benefits from being integrated on a renewable energy community. These benefits decrease when buildings are allowed to self-consume local generated energy prior to the sharing process as demand inequalities become less important for the computation of the considered sharing coefficients. The entire community also presents better performance in this case.